A Systematic Review of Social Media Use and Adolescent Identity Development - Avci, Hamide; Baams, Laura; Kretschmer, Tina (Adolescent Research Review, 2024)
Social media have become a new context for adolescent identity development. However, it is challenging to build a thorough understanding of how social media and identity development are related because studies refer to different facets of social media engagement and use diverse concepts related to identity. This review synthesizes research on the relationships between quantity and quality of social media use and different dimensions of identity development, including identity exploration and commitment, self-concept clarity, and identity distress. The search conducted across four databases yielded 4,467 records, of which 32 studies were included in the analysis, comprising 19,658 adolescents with a mean age of 16.43 years (SD = 1.81) and an age range of eight to 26 years. Active participation in social media, rather than the amount of time spent on it, was associated with more identity exploration. Authenticity on social media, not idealized self-presentation, correlated with higher self-concept clarity. Additionally, adolescents who engaged in comparisons on social media demonstrated higher levels of identity exploration and identity distress. Overall, it seems to matter more for identity development what young people do on social media than how much time they spend on it.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Adolescents; Identity development; Identity distress; Self-concept; Social media